UN economic conference in Africa - Hans Wallner (Intereconomics, 1973)
The 11th session of the UN Economic Commission for Africa and the second Ministerial Conference of that Organisation took place in Accra from February 19 to 23, 1973. The Commission—a regional organisation of the United Nations—has 41 independent African states as members.
Keywords: 330; Foreign Trade